Ruby lost and found - Li, Christina (Quill Tree Books, an imprint of HarperCollins Publishers, 2023)
"It's the summer after seventh grade, and Ruby Chu is feeling more lost than ever. Her best friends aren't speaking to her. She ended the year in detention. Her sister's about to leave for college. Ruby's still grieving her grandfather Ye-Ye when it seems like no one else is. And without Ye-Ye and his annual scavenger hunts across San Francisco, their hometown doesn't really feel like home anymore. Things get worse when Ruby's forced to spend the summer with her distant grandmother Nai-Nai in Chinatown. Then the looming shutdown of a beloved former scavenger hunt stop, May's Bakery, and a secret about Nai-Nai threaten to change everything. Even though Ruby feels out of place, maybe this summer of forming unexpected friendships and fighting to save the bakery will help Ruby reconnect with the world -- and discover what it means to find home again." --